A study of concentration of sugar mill effluents on properties of soil and types of micro-organisms present in the soil - Sangeeta, Sangeeta; Devi, Rani; Rani, Gita (Current Botany, 2017)
Â The work was undertaken to assess the effect of various concentrations like 0%, 25%, 50% and 100% of sugar mill effluents (SME) on soil properties and types of micro-oranisms present were also studied. With increased concentration of SME causes increase in Total Organic Carbon (TOC), pH, Electrical Conductivity (EC), Ca+2, Mg+2 etc. of the soil. Keywords: Sugar mill effluents, micro-organisms, Total Organic Carbon (TOC), Electrical Conductivity (EC).